Biomarcadores sanguíneos do estresse oxidativo em ratos normais e diabéticos tratados com N-acetilcisteína - Bairros, André Valle de (2009)
Diabetes mellitus (DM) is a metabolic disorder caused by decreased production and/or action of insulin which leads to hyperglycemia. This results in increased oxidative stress, which is related to several pathologies and, consequently, to cell damage. In this regard, studies investigating pro-drugs such as N-acetylcysteine (NAC) as a possible drug therapy are important. NAC is a drug with antioxidant capacity as well as a precursor of reduced glutathione (GSH), an important endogenous antioxidant. This study aimed to assess the levels of blood biomarkers of oxidative stress such as GSH, malondialdehyde (MDA), superoxide dismutase (SOD), catalase and glutathione peroxidase (GPx). In addition, we evaluated biomarkers of renal and hepatic function, blood glucose and glycated hemoglobin (HbA1C) and butyrylcholinesterase activity (BuChE) in healthy mice and alloxan- induced diabetic mice treated with NAC for 30 days. The groups were (n = 6): Control / saline; Control / NAC 25 mg / kg; Control / NAC 75 mg / kg; Diabetic / saline; Diabetic / NAC 25 mg / kg; Diabetic / NAC 75 mg / kg. Supplementation of NAC had no effect on blood glucose, HbA1C and biomarkers of renal and hepatic function in any group. The levels of GPx, GSH, catalase and MDA did not differ in the diabetic groups treated with NAC when compared to the diabetic / saline group. However, the levels of SOD in diabetic rats that received NAC were higher (p <0.05) when compared to the diabetic / saline group. Moreover, the levels of serum BuChE decreased in diabetic animals treated with NAC compared to diabetic / saline rats (p <0.05). The results of this study demonstrate that NAC did not significantly alter blood biomarkers of oxidative stress. However, NAC was shown to effect the enzymes SOD and BuChE in diabetic groups, indicating that these enzymes play an important role in DM and that further studies are needed to investigate the action of this drug and its relationship with SOD and BuChE in this endocrinopathy.